Perancangan Company Profile Desain Komunikasi Visual Universitas Negeri Padang melalui CD Interaktif - Muhammad Dahnil, Ishakawi, Syafwandi (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
AbstrackIn the days when this information is basic needs of society. In the development of tekonologi information is very readily obtainable. The current condition dkv unp must have a media promotion better or effective from media promotion formerly in the form of company profile that are packaged through cd interactive.